Studies toward the total synthesis of parvifolals A/B: an intramolecular o-quinone methide [4 + 2]-cycloaddition to construct the central tetracyclic core - Paymode, D. J.; Ramana, C. V. (ACS Omega, 2019)
Two different approaches funded upon the intramolecular [4 + 2]-cycloaddition of in situ generated o-quinone methides have been explored to construct the central tetracyclic core of parvifolals A/B. At the outset, a cross-pinacol coupling of 2-formyl tri-O-methyl resveratrol with 4-methoxysalicylaldehyde followed by acid treatment was found to provide the desired tetracyclic core with an internal olefin. The requisite pendant aryl group has been introduced by a Pd-catalyzed direct coupling of corresponding diazonium salt.